Novel sources of bioactive compounds in coconut (Cocos nucifera L.) water from different maturity levels and varieties as potent skin anti-aging strategies and anti-fatigue agents - Halim, Hani Hafeeza; Pak Dek, Mohd Sabri; Abdul Hamid, Azizah; Saari, Nazamid; Mohd Lazim, Mohd Izwan; Abas, Faridah; Ngalim, Ahmad; Ismail, Amin; Jaafar, Ahmad Haniff (Elsevier, 2022)
Coconut water (CW) is a popular natural hydration drink in tropical countries. It is rich in essential electrolytes, vitamins, minerals, and bioactive compounds with functional properties. Therefore, this work aimed to evaluate the functional properties (i.e., antioxidant and anti-aging activities) and to determine selected bioactive compounds in young and mature CW from the four most popular coconut varieties in Malaysia namely, Aromatic Green Dwarf (PDN), Malaysian Yellow Dwarf (MYD), MATAG (MYD × Tagnanan) and MAWA (MYD × West African Tall). Spectrophotometric and liquid chromatography methods were used to quantify the changes in the tested parameters. It is shown that the quantification of selected bioactive compounds and functional activities of CW displayed a mixed pattern at different maturation. Results from antioxidant, anti-aging activities, amino acids profile and bioactive compounds such as gallic acid, catechin, trans-zeatin, and dihydrozeatin were measured to decrease with the coconuts’ maturation. Meanwhile, the amount of kinetin, kinetin riboside and trans-zeatin riboside increased with the maturation of the coconuts. Specifically, CW from young MYD showed the highest antioxidant and anti-aging activities and possessed diverse bioactive compounds that could serve as novel sources of natural functional ingredients targeted for skin anti-aging. In addition, the sensory evaluation showed that the taste of young and mature CW is acceptable for consumption with the young PDN, young MYD and mature MYD displaying the highest score. To the best of our knowledge, the present work reported the first attempt to elucidate the inhibitory activities of CW towards elastase and collagenase enzymes.